2002
DOI: 10.1515/jpm.2002.046
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity not maternal glucose values correlates best with high rates of fetal macrosomia in pregnancies complicated by gestational diabetes

Abstract: The association of maternal glucose values and fetal macrosomia was limited to the fasting glucose values between 32-35 weeks while maternal obesity appeared to be a strong risk factor for macrosomia throughout pregnancies with GDM. In obese women the high fetal macrosomia rate did not appear be normalized by therapy based on maternal euglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
59
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 29 publications
12
59
1
4
Order By: Relevance
“…So, FPG is a simple indicator for identifying high risk women with GDM. Earlier reports noted that the fasting glucose value was better than the postchallenge glucose levels in identifying LGA risk (21,24,25). Similarly, Retnakaran and cols.…”
Section: Discussionmentioning
confidence: 88%
“…So, FPG is a simple indicator for identifying high risk women with GDM. Earlier reports noted that the fasting glucose value was better than the postchallenge glucose levels in identifying LGA risk (21,24,25). Similarly, Retnakaran and cols.…”
Section: Discussionmentioning
confidence: 88%
“…Among more than 38 000 deliveries, obese women were significantly more likely to have babies with a cardiac anomaly (odds ratio (OR) 6.5; 95% confidence interval (95% CI) 1.2-34.9; P ¼ 0.025). Two studies by Shaw et al 6,8 found an increased risk for neural tube defects in the offspring of obese women. In addition, there is a known correlation between maternal obesity and diabetes, which also carries increased risk for fetal anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a known correlation between maternal obesity and diabetes, which also carries increased risk for fetal anomalies. 3,6 Finally, Schwarzler et al 19 randomized 1206 women and compared the ability to complete the fetal anatomy scan at 18, 20, or 22 weeks. They concluded that in an unselected population, second-trimester ultrasound screening at 20-22 weeks rather than 18 weeks was easier to perform and less likely to require an additional scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the non-diabetic population, the sex of the infant, and maternal age, parity and time since last pregnancy have been shown to explain about 20% of the variance in birthweight [22]. The birthweight of the parents and maternal pre-pregnancy BMI have also been shown to correlate with the birthweight of the offspring [8,[35][36][37]. In the present study, maternal BMI, maternal age and time elapsed since last pregnancy were not significantly related to the birthweight of the second-born infant.…”
Section: Discussionmentioning
confidence: 99%